2009
DOI: 10.1017/s0144686x09990523
|View full text |Cite
|
Sign up to set email alerts
|

How health affects retirement decisions: three pathways taken by middle-older aged New Zealanders

Abstract: Concerns about the economic impact of an ageing population have triggered many developed countries to advance policies that attempt to extend working lives and discourage early retirement. There is considerable evidence of a relationship between poor health and early retirement, but some researchers have suggested that there is a ‘justification bias’ in claims that ill-health is the cause of retirement. This paper reports a longitudinal qualitative study that interviewed 60 New Zealanders aged between 55 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 41 publications
2
45
0
2
Order By: Relevance
“…Improving the Early Retirement Model showed that high social support of colleagues and supervisor and a positive attitude of the partner with respect to early retirement also influenced early retirement directly, and that having a partner was only directly related to early retirement. The finding that work ability and the opportunity to work mediate the relation between health, job characteristics, skills and knowledge, and social factors is in line with previous qualitative research (14,22,23). Unexpectedly, work engagement did not mediate the relation between these determinants and early retirement, although previ- de Wind et al ous qualitative research suggested this (14).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Improving the Early Retirement Model showed that high social support of colleagues and supervisor and a positive attitude of the partner with respect to early retirement also influenced early retirement directly, and that having a partner was only directly related to early retirement. The finding that work ability and the opportunity to work mediate the relation between health, job characteristics, skills and knowledge, and social factors is in line with previous qualitative research (14,22,23). Unexpectedly, work engagement did not mediate the relation between these determinants and early retirement, although previ- de Wind et al ous qualitative research suggested this (14).…”
Section: Discussionsupporting
confidence: 84%
“…Qualitative research suggested that the ability, motivation, and opportunity to work mediate the relationship between determinants in the domains health, job characteristics, skills and knowledge, and social and financial factors, on the one hand, and early retirement on the other hand (14,22,23). For example, employees experiencing physically demanding work or high work pressure retired early because they felt their work demands reduced their ability to continue working (14).…”
Section: De Wind Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…A common policy response to the issue of population ageing in Western countries is to postpone retirement to older ages (Hamblin 2010;Pond et al 2010). For example, in the UK, under the Pensions Act 2011, the state pension age for women will increase from 60 to 65 by 2018.…”
Section: Introductionmentioning
confidence: 99%
“…People who have health problems are more likely to withdraw from the labour market and are expected to be less inclined -and able -to re-enter the labour market after early retirement, even if the job is more flexible and less taxing than the work they used to do (Pond et al 2010). Table).…”
Section: Figure 2 Probability Of Taking Up Bridge Employment By Levelmentioning
confidence: 99%